Integrated palynology and sedimentology of the Mississippian of the Tisdafine Basin (Eastern Anti-Atlas, Morocco) - Talih, Amine; Ţabără, Daniel; Slimani, Hamid; Saadi, Mohamed; Benmlih, Abdelouahed; Aboutofail, Salma (Swiss journal of palaeontology, 2022)
The Mississippian (Tournaisian–Visean) of the Jbel Asdaf area in the Tisdafine Basin (Eastern Anti-Atlas, Morocco) has been, for the first time, the subject of a palynological study. This work aims first to describe the lithological and the paleontological composition of the Aït Yalla and Tinerhir Formations, then to refine the age, reconstruct the paleoenvironment and assess the thermal maturity of the organic matter. The studied section is subdivided, from oldest to youngest, into three intervals, according to their lithological and paleontological compositions. Lithologically, the lower interval (lower part of the Aït Yalla Formation) and middle interval (upper part of the Aït Yalla Formation and basal part of the Tinerhir Formation) consist mostly of clay shales and green shales, respectively, both alternating with limestone or sandstone beds. The upper interval (upper part of the Tinerhir Formation) is dominated by sandstones, also alternating with pelitic-sandstone or limestone beds. The kerogen delivered by the analyzed samples is mostly of continental origin, composed mainly of opaque phytoclasts, while translucent phytoclasts and miospores are less represented. Marine fraction, consisting mainly of granular amorphous organic matter and some phytoplankton, are rare. Biostratigraphically, the late Visean Tripartites vetustus – Rotaspora fracta (VF) miospore Zone of the Western Europe biozonal scheme is recognized with some regards in the Tinerhir Formation, based on the first occurrence of the miospore Rotaspora cf. knoxi . Vallatisporites aff. ciliaris is another biostratigraphic marker taxon of the assemblage, whose the last occurrence marks the end of the VF Biozone at the top of the analyzed section. Qualitative and quantitative parameters of the different palynofacies constituents (e.g., shape, size, % of opaque and translucent phytoclasts) show, from the base to the top of the section, a gradual transition from a distal marine environment generally recognized in the Aït Yalla Formation towards an intermediate marine environment in the Tinerhir Formation, suggesting a sea-level fall. Optical analyses performed on the color of palynomorphs, mainly spores, suggest a thermal maturity, ranging from late mature to early post-mature stage for most of the analysed samples, with a burial depth and a temperature of at least 3300 m and 90 °C, respectively.